Blood levels of growth and progression factors in patients with locally advanced breast cancer during neoadjuvant chemotherapy - E. M. Frantsiyants; N. Yu. Samaneva; L. Yu. Vladimirova; A. E. Storozhakova; E. A. Kalabanova; S. N. Kabanov; A. V. Tishina (Южно-Российский онкологический журнал, 2021)
Purpose of the study. An analysis of blood levels of TGF-β, TGFR2, TNF-α, TNF-αR1, TNF-αR2, CD44 and MMP9 in patients with various biological subtypes of breast cancer receiving neoadjuvant chemotherapy.Materials and methods. This article presents an analysis of levels of growth and progression factors (TGF-β, TGFR2, TNF-α, TNF-αR1, TNF-αR2, CD44 and MMP9) in the blood of 162 patients with various biological subtypes of locally advanced breast cancer receiving 8 cycles of neoadjuvant chemotherapy.Results. Levels of TGF-β, TGFR2, TNF, TNF-α, TNFR1, TNFR2, CD44, MMP9 in patients with all BC subtypes were high before the treatment. After chemotherapy cycles, the values decreased statistically significantly in all BC subtypes: CD44 decreased by 25.2 %, 30 % and 54.7 % in luminal A, luminal B and TNBC, respectively; TNFα– by 26.2 %, 48.3 % and 50.8 %, respectively; TNFα-R1 – by 52.1 %, 39.2 % and 50.3 % respectively; TNFα-R2 – by 31.7 %, 32.8 % and 41.9 % respectively; MMP9 – 35.3 %, 32.6 % and 43.3 % respectively.Conclusions. We identified a combination of growth and progression factors which determines the chemotherapy sensitivity and resistance in all subtypes of breast cancer; so, a decline in the levels of TGF-β, TNFα, MMP9 and CD44 after neoadjuvant chemotherapy predicts further remission for at least 3 years. On the contrary, stabilization or an increase of these indicators leads to the early tumor progression.